MiR-218-5p Mediates Myocardial Fibrosis after Myocardial Infarction by Targeting CX43 - Sun, Bing; Zhao, Cuimei; Mao, Yu (Current Pharmaceutical Design, 2021)
Background: Myocardial fibrosis after myocardial infarction (MI) has been considered a core factor in the deterioration of cardiac function. Previous studies have shown that miRNA plays an important role in various pathophysiological processes of the heart. However, the role of miRNA in myocardial fibrosis regulation after MI remains unclear. In the present study, we documented that miR-218-5p was significantly decreased in myocardial fibroblasts after MI. Methods: The miRNA expression profiles of MI were downloaded from GEO Datasets. The expression of a fibrosis-related gene in vivo and in vitro was analyzed by RT-PCR, western blotting, and immunohistochemical staining. Results: Total 7 up- and 9 downregulated common miRNAs were found in the two profiles. Among these common genes, miR-218-5p was downregulated in the MI mice. MiR-218-5p mediated the myocardial fibrosis in vivo and in vitro. Mechanistically, we found that GJA1 (CX43) may be the target of miR218-5p, and overexpressed CX43 can partly block the function of miR-218-5p in fibrosis inhibition. Conclusion: Our results suggested that miR-218-5p plays an important role in myocardial fibrosis after MI by targeting CX43. Thus, miR-218-5p promises to be a potential diagnosis and treatment of myocardial fibrosis after MI.
Keywords: GJA1 (CX43)